EVALUATION OF PHARMACOECONOMICS AWARENESS AND ITS APPLICATION AMONG POSTGRADUATES OF A TERTIARY CARE HOSPITAL: A CROSS-SECTIONAL OBSERVATIONAL STUDY - Tabassum, Rehana; Hussain, Syed Sajad; BANDAY, MUDDASIR (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: Pharmacoeconomics (PE) is a branch of health economics which focuses particularly on the cost and benefit of drug therapy. Postgraduate students form the first line of the health care delivery system, especially in government run hospitals; therefore, it is essential that they need to be aware of the concept of PE. The main objective of the study was to assess the extent of knowledge and awareness of PE and its methods of application among medical professionals who are doing postgraduation in various departments. Methods: This study was conducted at Sheri Maharaja Hari Singh (SMHS) Hospital, a tertiary care hospital associated with Government Medical College, Srinagar. Self-administered questionnaire was distributed among 100 students, out of which 78 completely filled questionnaires were finally used for statistical analysis. The statistical analysis was performed using Statistical Package for the Social Sciences (SPSS, version 19, Chicago, IL, USA). Results: It was observed that most of the participants were willing to participate in the study, and a good proportion of them (45%) were aware about the concept of PE. However, the majority of the respondents had little knowledge about the principles of PE and only 16% of them responded positively. When it comes to the application of PE, it was found that only 9% are applying these principles in their day to day clinical practice. Conclusion: There is need to sensitize the health care providers to the concept of PE at undergraduate level so that they will be able to utilize their knowledge of PE, in their clinical practice in the future. Keywords: Pharmacoeconomics, Postgraduate students, Level of knowledge, Methods of application.